2023
DOI: 10.1021/acs.inorgchem.3c00002
|View full text |Cite
|
Sign up to set email alerts
|

C(NH2)3(I3O8)(HI3O8)(H2I2O6)(HIO3)4·3H2O: An Unprecedented Asymmetric Guanidinium Polyiodate with a Strong Second-Harmonic-Generation Response and a Wide Band Gap

Abstract: Herein, we report an unprecedented asymmetric guanidinium polyiodate, namely, C­(NH2)3(I3O8)­(HI3O8)­(H2I2O6)­(HIO3)4·3H2O (1). The title compound was obtained via the hybridization of polyiodate anions and planar π-conjugated C­(NH2)3 +; meanwhile, its strong second-harmonic-generation (SHG) response (2.1 × KDP, where KDP = KH2PO4) and wide band gap (3.89 eV) were mainly dominated by the synergy effect of the aforementioned structural units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(50 reference statements)
2
9
0
Order By: Relevance
“…The UV–vis–near-infrared (NIR) diffuse reflectance spectra reveal the same band gaps of 3.65 eV and the same UV absorption cutoff edge of 321 nm for α- and β-(C 4 H 5 N 2 O)­(IO 3 )·HIO 3 (Figure S6). The optical band gaps are wider than those of metal iodates reported such as CsVO 2 F­(IO 3 ) (2.34 eV), Nb 2 O 3 (IO 3 ) 2 (SO 4 ) (3.25 eV), and [C­(NH 2 ) 3 ] 2 Mo 2 O 5 (IO 3 ) 4 ·2H 2 O (3.55 eV) but are smaller than those of [ o -C 5 H 4 NHOH] 2 [I 7 O 18 (OH)]·3H 2 O (3.90 eV), (C 6 H 20 N 3 )­(IO 3 ) 3 ·2H 2 O (4.24 eV), and (C 2 H 10 N 2 )­(IO 3 ) 2 ·HIO 3 (4.6 eV). ,,,,,, The small band gaps of α- and β-(C 4 H 5 N 2 O)­(IO 3 )·HIO 3 among the organic–inorganic hybrid iodates can be attributed to a greater overlap among the O 2p, N 2p, and C 2p orbitals in (C 4 H 5 N 2 O) + .…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The UV–vis–near-infrared (NIR) diffuse reflectance spectra reveal the same band gaps of 3.65 eV and the same UV absorption cutoff edge of 321 nm for α- and β-(C 4 H 5 N 2 O)­(IO 3 )·HIO 3 (Figure S6). The optical band gaps are wider than those of metal iodates reported such as CsVO 2 F­(IO 3 ) (2.34 eV), Nb 2 O 3 (IO 3 ) 2 (SO 4 ) (3.25 eV), and [C­(NH 2 ) 3 ] 2 Mo 2 O 5 (IO 3 ) 4 ·2H 2 O (3.55 eV) but are smaller than those of [ o -C 5 H 4 NHOH] 2 [I 7 O 18 (OH)]·3H 2 O (3.90 eV), (C 6 H 20 N 3 )­(IO 3 ) 3 ·2H 2 O (4.24 eV), and (C 2 H 10 N 2 )­(IO 3 ) 2 ·HIO 3 (4.6 eV). ,,,,,, The small band gaps of α- and β-(C 4 H 5 N 2 O)­(IO 3 )·HIO 3 among the organic–inorganic hybrid iodates can be attributed to a greater overlap among the O 2p, N 2p, and C 2p orbitals in (C 4 H 5 N 2 O) + .…”
Section: Resultsmentioning
confidence: 75%
“…The SHG signals of α- and β-(C 4 H 5 N 2 O)­(IO 3 )·HIO 3 are about 6.4 and 0.9 times that of a KDP (particle size 210–300 μm), respectively, and α- and β-(C 4 H 5 N 2 O)­(IO 3 )·HIO 3 are type-I phase-matchable (Figure ). The SHG response of α-(C 4 H 5 N 2 O)­(IO 3 )·HIO 3 is stronger than those of some reported pyrimidine compounds and iodates, such as (C 4 H 6 N 3 ) + (H 2 PO 3 ) − (2 × KDP), [C­(NH 2 ) 3 ] 2 Mo 2 O 5 (IO 3 ) 4 ·2H 2 O (5 × KDP), and C 6 H 14 N 4 O 2 ·2HIO 3 (1 × KDP). ,,, The SHG effect of α-(C 4 H 5 N 2 O)­(IO 3 )·HIO 3 is stronger than most organic–inorganic hybrid iodates, which distinguishes the (C 4 H 5 N 2 O) + cation as a remarkable group. The favorable alignment of IO 3 groups (the same direction) is beneficial to the relatively superior SHG effect of α-(C 4 H 5 N 2 O)­(IO 3 )·HIO 3 .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Hence, it becomes necessary to employ appropriate strategies to obtain NCS crystals. Current theoretical and experimental studies have demonstrated that the rational combination of two or more asymmetric units serves as an effective strategy for synthesizing NLO materials, facilitating the generation of strong SHG effects. Typical asymmetric units include: (1) metal cations containing stereochemistry active lone pair (SCALP) electrons, such as Bi 3+ , Pb 2+ , Sb 3+ , Sn 2+ , etc. ; (2) twisted transition-metal polyhedrons involving d 0 and d 10 cations, such as Mo 6+ , Ti 4+ and Zn 2+ ; and (3) anions with planar π-conjugated structures, such as BO 3 3– , CO 3 2– , NO 3 – , etc. It is worth noting that among these units, metal cations with SCALP can form highly anisotropic coordination polyhedrons, which contribute to enhancing the SHG response of NCS materials.…”
Section: Introductionmentioning
confidence: 99%
“…According to the anionic group theory, the iodate anionic group IO 3 is an NLO-active unit with significant microscopic second-order NLO susceptibility due to its asymmetric pyramidal coordination geometry and stereochemically active lone pair electrons, which is beneficial to the formation of non-centrosymmetric crystal structures with outstanding NLO properties. Metal iodates have been extensively studied as NLO materials. A large number of new iodates with strong SHG effects have been discovered, such as Li 2 Ti­(IO 3 ) 6 (500 × α-SiO 2 ), CsMoO 3 (IO 3 ) (400 × α-SiO 2 ), and K 2 Au­(IO 3 ) 5 (1.0 × KTiOPO 4 ) . However, no research work regarding iodate MNWs has been reported.…”
mentioning
confidence: 99%